Clinical pattern of checkpoint inhibitor-induced liver injury in a multicentre cohort - Lina Hountondji; Christophe Ferreira De Matos; Fanny Lebossé; Xavier Quantin; Candice Lesage; Pascale Palassin; Valérian Rivet; Stéphanie Faure; Georges-Philippe Pageaux; Éric Assenat; Laurent Alric; Amel Zahhaf; et al. (JHEP Reports, 2023)
Background & Aims: Immune checkpoint inhibitors (ICIs) have changed the landscape of cancer therapy. Liver toxicity occurs in up to 25% of patients treated with ICIs. The aim of our study was to describe the different clinical patterns of ICI-induced hepatitis and to assess their outcome. Methods: We conducted a retrospective observational study of patients with checkpoint inhibitor-induced liver injury (CHILI) discussed in multidisciplinary meetings between December 2018 and March 2022 in three French centres specialised in ICI toxicity management (Montpellier, Toulouse, Lyon). The hepatitis clinical pattern was analysed by the ratio of serum alanine aminotransferase (ALT) and alkaline phosphatase (ALP) (R value = (ALT/ULN)/(ALP/ULN)) for characterisation as cholestatic (R ≤2), hepatocellular (R ≥5), or mixed (2 <R <5). Results: We included 117 patients with CHILI. The clinical pattern was hepatocellular in 38.5%, cholestatic in 36.8%, and mixed in 24.8% of patients. High-grade hepatitis severity (grade ≥3 according to the Common Terminology Criteria for Adverse Events system) was significantly associated with the hepatocellular hepatitis (p <0.05). No cases of severe acute hepatitis were reported. Liver biopsy was performed in 41.9% of patients: granulomatous lesions, endothelitis, or lymphocytic cholangitis were described. Biliary stenosis occurred in eight patients (6.8%) and was significantly more frequent in the cholestatic clinical pattern (p < 0.001). Steroids alone were mainly administered to patients with a hepatocellular clinical pattern (26.5%), and ursodeoxycholic acid was more frequently used in the cholestatic pattern (19.7%) than in the hepatocellular or mixed clinical pattern (p <0.001). Seventeen patients improved without any treatment. Among the 51 patients (43.6%) rechallenged with ICIs, 12 (23.5%) developed CHILI recurrence. Conclusions: This large cohort indicates the different clinical patterns of ICI-induced liver injury and highlights that the cholestatic and hepatocellular patterns are the most frequent with different outcomes. Impact and Implications: ICIs can induce hepatitis. In this retrospective series, we report 117 cases of ICI-induced hepatitis, mostly grades 3 and 4. We find a similar distribution of the different patterns of hepatitis. ICI could be resumed without systematic recurrence of hepatitis.